Krajina (Landscape) - lexical evolution assisted discourse analysis - Hořejší, Michal (Bohemica Olomucensia, 2017)
The paper deals with a position of a lexeme krajina (landscape) which appears in the texts focused on the topic of Šumava (Bohemian forest). The paper compared texts about Šumava with current usage in the Czech national corpus (SYN2010) and with a diachronic material also. The paper tries to describe the ways of specific lexical actualizations in the discourse on Šumava.
Keywords: lexical evolution; discourse analysis; discourse; context; diachrony; Old Czech; corpus; Bohemian forest